Optimization of Reactions Opening Cyclic Ring of Pentose Sugar Derivatives through Dithioacetalisation Reactions - Nuriman, Nuriman (Jurnal ILMU DASAR, 2016)
Ring-opening reaction of cyclic pentose sugar derivatives of 2,3,4-Tri-O-benzyl- D-xylopyranoseto derivatives of acyclic 2,3,4-Tri-O-benzyl-D-xylose-Dipropyl dithioacetal been done andoptimized. The reaction was performed using a precursor propanathiol with concentrated HCl.Optimization of reaction conditions was conducted by varying propanathiol concentration,reaction time and optimization of the reaction temperature which the product ioslation conductedusing a variety of solvents. The results of this reaction was obtained 2,3,4-Tri-O-benzyl- Dxylose-Dipropyl dithioacetal with the highest randemen (97%), better than the previous reactionthrough propanathiol excessive concentration, reaction time of 2 hours and the temperature of thereaction at room temperature. Product Isolations using solvent dikloromathane more effectivethan the use of other organic solvents. Purification of reaction products is done through a columnchromatography using a solvent mixture of 20% ethyl acetate-hexane.Keywords: Optimization, Cyclic Ring, Dithioasetalisasi